EXPLORING THE SEMANTIC SIGNIFICANCE OF LEXICON IN EBEG TRADITIONAL ART OF KEBUMEN REGENCY - Nur Indah Octaviani; Nur Fateah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study explores the relationship between language and culture through the traditional art form of ebeg in Kebumen Regency which functions as a vital expression of local identity and values. This study aims to (1) classify the lexicon used in ebeg based on lexical and cultural meanings, and (2) reveal the local wisdom contained in the performance. Using qualitative descriptive methods within an ethnographic framework, data were collected through observation and interviews with community elders, studio leaders, and ebeg players. The research findings reveal various lexicons related to ebeg which are categorized according to elements such as uborampe (ritual offerings), dance movements, tembang (traditional songs), and performance attributes (sandhangan). Furthermore, this study highlights the philosophical and moral values ??conveyed through these linguistic and cultural expressions which underline the role of ebeg in preserving Kebumen's local heritage